Effects of co-digestion of camel dung and municipal solid wastes on quality of biogas, methane and biofertilizer production - Kheira, Benaissa Nawel; Dadamoussa, Belkheir; Bendraoua, Abdelaziz; Mel, Maizirwan; Labed, Brahim (Akademia Baru, 2017)
Biogas and biofertilizer production from anaerobic digestion of local organic solid waste in Algeria is an attractive choice for greener and cleaner environment. In this paper, the study focused on the effect of co-digestion of municipal solid organic wastes (MSW) and camel dung (CD) for the quality production of biogas (methane) and bio fertilizer products. The concentration of methane production is the preeminent aim of this work. The experiment was set by feedstocks preparation where organic waste was mixed with tap water at 1:1 ratio and it allowed to digest at temperature of 40 °C. The operating hydraulic retention time (HRT) was set at 35 days. Physicochemical properties of feedstocks and constituent elements of the digestate were determined by American Public Health Association methods. The experimental study indicated that underdefined operational conditions such as constant organic loading rate (OLR) of 0.6 kg per day, hydraulic retention time (HRT) of 35 days and temperature of 40C from MSW and MSW and CD mixtures of ratio at one to one resulted in a higher methane production (57.3%) compared to monodigestion of camel dung that produced 45.6% of CH4) in a pH range between 7.0 to 8.1. The improvement has also found related to high biodegradability of the MSW, the slight ammonium concentration, the optimization of the carbon-to-nitrogen ratio (C/N 25.8:1) and to the well-balanced nutrients content of the feedstock. The digestate coming from anaerobic co-digestion has also used as bio-fertilizer and this by-product has a benefit to avoid the harmful effect in the digester system and in the surrounding environment. It is shown clearly that the MSW and CD are highly desirable substrates for anaerobic co-digestion with regards to their good biodegradability, high methane yield and good bio-fertilizer quality